PENGGUNAAN REAKTOR SERI UNTUK MENGURANGI ARUS HUBUNG SINGKAT - Wahyudin SN; Retno Aita Diantari; Guntur Febby Ramadhan (Sutet, 2015)
Three-phase short circuit current at the busbars of 20 kV power transformers 150/20 kV substation is the largest fault current value to be able to cut off the circuit breaker. Breaking current circuit breaker owned by either side of the 150 kV and 20 kV should be able to break the short circuit current is within a certain time. The normal operation of power transformers 150/20 kV substation in a parallel on the side of 150 kV, 20 kV, while the side of each transformer supplying a load busbar respectively. Whereas in certain circumstances the transformer works parallel with the other transformer to supply the load together, short circuit current on the busbar 20 kV become magnified. To reduce that short circuit current on the busbar, then at 20 kV busbar coupling mounted reactor series. This paper will discuss how much value of the reactance of the reactor 20 kV busbar coupling in order to obtain short-circuit current value desired by considering the voltage droop allowed on the busbar.